Strategy for The Development of Sagon Cake Products in Cipedes Village Ciniru District, Kuningan Regency - Lia Marliani; Rini Ratna Nafita Sari (⁠⁠Jurnal Literasi Indonesia, 2024)
A product development strategy is a strategy for the development of original products, product improvements, and new brands. Products must be created to pay attention to sales so that they continue to increase, namely by adding new products or developing old products. The purpose of this study is to find out the Development Strategy of Segon Cake Products in Cipedes Village, Ciniru District, Kuningan Regency and to find out the Obstacles to the Development Strategy of Segon Cake Products in Cipedes Village, Ciniru District, Kuningan Regency. In this study, the method used is a case study method with a qualitative approach. Qualitative research aims to gain a deep understanding of the situation at hand. This study concludes that the home industry development strategy  of Sagon Cake products is influenced by the factors of sellers starting a business by looking for customers, increasing the number of employees, sellers with an offline system, needing funds or double capital, improving existing products, adding flavor variants to old products. Then there are 2 obstacles to product development strategies in  the Sagon Cake home industry, namely internal and external problems. Internally, it includes the soaring price of glutinous rice flour raw materials, the scarcity of grated coconut supply, and unstructured operational activities.